Isolation and Fear of Deportation: Intersectional Barriers to Well‐Being Among Latina Farmworkers in Southwestern Idaho. (3rd December 2020) - Meierotto, Lisa; Castellano, Rebecca L. Som; Curl, Cynthia
Abstract: Latina farmworkers in rural Idaho live with geographic isolation, fear of deportation, gender disparities, and income inequalities. While economic and social challenges have existed for decades, fear and isolation have become more acute during the Trump administration. Utilizing interview, survey, and focus group data, we identify multiple ways in which Latina farmworkers struggle with policy‐exacerbated isolation. We find that experiences of isolation intersect with gender disparities and economic inequalities, and this ultimately affects women's well‐being.